1992
DOI: 10.1136/jcp.45.7.561
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of beta 2-glycoprotein-1 (apolipoprotein H) and other markers of tubular malfunction in "non-tubular" renal disease.

Abstract: accounts for their increased urinary excretion in renal tubular disorders. Unfortunately, finding them in excess is not specific to renal tubular disease because all three are excreted in increased quantity whenever the endogenous creatinine clearance is reduced-to 25-30 ml/minute in the case of RBP and /i2M,2 and to less than 55 ml/minute in the case of a1m.3Increased excretion of N-acetyl-f,-D-glucosaminidase (NAG), an enzyme found in the lysosomes of proximal renal tubule cells, should be more specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Increased excretion of NAG, an enzyme found in the lysosomes of proximal renal tubular cells, has been demonstrated to be more specific for renal tubular pathology (15). The molecular weight of NAG is large enough to preclude passage through the normal glomerular basement membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased excretion of NAG, an enzyme found in the lysosomes of proximal renal tubular cells, has been demonstrated to be more specific for renal tubular pathology (15). The molecular weight of NAG is large enough to preclude passage through the normal glomerular basement membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidants are major products of inflammation and lipids peroxides have been shown to increase in the plasma of burn animals and patients (6,(13)(14)(15)(16)(17)(18)(19)(20)(21). Free radical production is associated with inflammation, and circulating lipid peroxides have been shown to increase in burn patients during the first week post injury (6,21,22,24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many of the data available were from children with the nephrotic syndrome using random urine samples [17]. Hitherto comment could not be made on the effects of mild-tomoderate renal impairment in patients with comparable proteinuria but different pathologies [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was suggested that it had a potential to be used as marker of tubular injury [38]. Several reports indicate that APOH is the antigen of the antiphospholipid antibodies and also behaves as an acutephase reactant [39].…”
Section: Discussionmentioning
confidence: 99%